Simultaneous effect of nitrogen, trifluoromethyl and dimethyl amino group on the radical trapping capacity of diphenylamine: a quantum chemical study - Thao, Pham Thi Thu; Thong, Nguyen Minh; Hai, Pham Thanh; Trang, Vo Quoc; Binh, Tran Thuc; Nam, Pham Cam (Vietnam Journal of Science and Technology, 2020)
In order to maximize the peroxyl radical trapping capacity of diphenynlamines, the substituents such as N, NMe2, and CF3 are suggested to add to their phenolic rings. The reasonable combination of these substituents at right position can reduce the bond strength of the N-H bond, but still keep the derivatives stable in air